Sacral tuberculosis :an atypical manifestation - Si Mirah, Faisal Amir; Jasni, Muhammad Jasfizal; Mor Japar Khan, Ed Simor Khan; Karupiah, Rajandra Kumar; Zakaria@Mohamad, Zamzuri (2018)
BACKGROUND Sacral tuberculosis (TB) is extremely rare and its unusual entity might delay the diagnosis and treatment of this treatable disease.